MICROARTROPODOS EN SUELOS DE BOSQUES DE NOTHOFAGUS PUMILIO EN PARQUES NACIONALES DE CHILE - Covarrubias, Rene; Covarrubias, Cecilia; Mellado, Ignacio (Acta Entomológica Chilena, 2022)
In a set of 11 forests of Nothofagus pumilio, in different National Parks, from "Laguna Laja" to "Pérez Rosales", the soil microarthropods were studied. The analysis of the abundances of the most frequent higher taxa shows significant variation, according to the individual forests, lo the season of the year and to the height of the trees.